A Treasure of Masterpieces
The artistic treasure of Washingtonïs National Gallery of Art are carefully expained in this part program hosted by former Gallery director, J. Carter Brown. The first part tells the fascinating story of how this Gallery came into being while the second part gives the viewer a guided tour of some on the fines work in the Galleryïs outstanding collection